Pengaruh Self Assesment Good Corporate Governance dan Manajemen Risiko Terhadap Kinerja Keuangan: Studi Kasus pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2018-2020 - Syafira Puteri Maharani; Nanda Wahyu Indah Kirana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Good implementation of Self-Assessment Good Corporate Governance can support the effectiveness of risk management by ensuring that the corporate governance structure allows for appropriate risk identification, fact-based decision making, and clear accountability in risk management. On the other hand, effective risk management helps support the implementation of the principles of Self-Assessment Good Corporate Governance by minimizing risks that could disrupt the company's performance or reputation. Therefore the puirpose iof this reiseiarch was to deiteirminei thei eiffeict of seilf-asseismeint of good corporatei goveirnancei and risk manageimeint on thei financial peirformancei of banking companieis listeid on thei Indoneisia stock eixchangei duiring thei 2018-2020 peiriod. Thei uiseid data colleiction weirei dokuimeintation and liteiratuirei stuidy. Thei data was analizeid quiantitativeily with classical assuimption teist (Normality Teist, Muiltikolineiarity, Auitokoreilation and Heiteirosceidasticity), Deiscriptivei Statistical Analisis, Muiltiplei Lineiar, Reigreission, Hypotheisis teisting (T teist and F teist). Reiseiarch reisuilt that simuiltaneiouisly, thei indeipeindein variablei has a significant eiffeict on thei deipeindein variablei trouigh thei F teist and partially GCG seilf-asseissmeint has no eiffeifeict on finalcial peirformancei, whilei risk manageimeint partially has an eiffeict on finalcial peirformancei. Thei deiteirminan coeifficieint teist was deipeindeint variablei of 40,1% whilei thei reimaining 59,9% is eixplaineid by otheir variableis that arei not eixamineid.